2018
DOI: 10.1159/000494209
|View full text |Cite
|
Sign up to set email alerts
|

The 12-Word Philadelphia Verbal Learning Test Performances in Older Adults: Brain MRI and Cerebrospinal Fluid Correlates and Regression-Based Normative Data

Abstract: Background/Aims: This study evaluated neuroimaging and biological correlates, psychometric properties, and regression-based normative data of the 12-word Philadelphia Verbal Learning Test (PVLT), a list-learning test. Methods: Vanderbilt Memory and Aging Project participants free of clinical dementia and stroke (n = 230, aged 73 ± 7 years) completed a neuropsychological protocol and brain MRI. A subset (n = 111) underwent lumbar puncture for analysis of Alzheimer’s disease (AD) and axonal integrity cerebrospin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…; Meeter et al, 2016; Meeter, Vijverberg, et al, 2018; van der Ende et al, 2020). The Gothenburg Mild Cognitive Impairment Study (Bjerke et al, 2009; Brinkmalm et al, 2014; Rolstad, Berg, et al, 2015; Wallin et al, 2016) was used in three studies, the Mayo Clinic Study of Ageing (Mielke, Syrjanen, Blennow, Zetterberg, Skoog, et al, 2019; Mielke, Syrjanen, Blennow, Zetterberg, Vemuri, et al, 2019; Roberts et al, 2008) in two studies, the Vanderbilt Memory and Ageing Project (Gifford et al, 2018; Jefferson et al, 2016; Osborn et al, 2019) in two studies and finally, the University of California San Diego (UCSD) Shiley‐Marcos Alzheimer's Disease Research Center (Galasko et al, 2019; Xiao et al, 2017) in two studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…; Meeter et al, 2016; Meeter, Vijverberg, et al, 2018; van der Ende et al, 2020). The Gothenburg Mild Cognitive Impairment Study (Bjerke et al, 2009; Brinkmalm et al, 2014; Rolstad, Berg, et al, 2015; Wallin et al, 2016) was used in three studies, the Mayo Clinic Study of Ageing (Mielke, Syrjanen, Blennow, Zetterberg, Skoog, et al, 2019; Mielke, Syrjanen, Blennow, Zetterberg, Vemuri, et al, 2019; Roberts et al, 2008) in two studies, the Vanderbilt Memory and Ageing Project (Gifford et al, 2018; Jefferson et al, 2016; Osborn et al, 2019) in two studies and finally, the University of California San Diego (UCSD) Shiley‐Marcos Alzheimer's Disease Research Center (Galasko et al, 2019; Xiao et al, 2017) in two studies.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies used SIMOA assays. Of the included 67 studies, only 29 reported the intra‐assay coefficient of variability (CV) (Abu‐Rumeileh et al, 2018; Bartos et al, 2011; Bendlin et al, 2012; Bjerke et al, 2009; Brinkmalm et al, 2014; Casaletto et al, 2017; Chatterjee, Del Campo, et al, 2018; Dhiman et al, 2020; Gifford et al, 2018; Hellwig et al, 2015; Hoglund et al, 2017; Kirsebom et al, 2018; Kvartsberg, Duits, et al, 2015; Lim et al, 2019; Meeter et al, 2016; Meeter, Gendron, et al, 2018; Meeter et al, 2019; Meeter, Vijverberg, et al, 2018; Mielke, Syrjanen, Blennow, Zetterberg, Vemuri, et al, 2019; Öhrfelt et al, 2019; Osborn et al, 2019; Rolstad, Jakobsson, et al, 2015; Sandelius et al, 2019; Skillback et al, 2014; Teitsdottir et al, 2020; van der Ende et al, 2020; Wellington et al, 2016; Zetterberg et al, 2016) and only 22 reported inter‐assay CVs (Abu‐Rumeileh et al, 2018; Bartos et al, 2011; Bjerke et al, 2009; Brinkmalm et al, 2014; Chatterjee, Del Campo, et al, 2018; Dhiman et al, 2020; Hellwig et al, 2015; Hoglund et al, 2017; Kvartsberg et al, 2015; Meeter et al, 2016; Meeter, Gendron, et al, 2018; Meeter et al, 2019; Meeter, Vijverberg, et al, 2018; Mielke, Syrjanen, Blennow, Zetterberg, Skoog, et al, 2019; Mielke, Syrjanen, Blennow, Zetterberg, Vemuri, et al, 2019; Mouton‐Liger et al, 2020; Rolstad, Jakobsson, et al, 2015; Sandelius et al, 2019; Singh et al, 2016; Teitsdottir et al, 2020; van der Ende et al, 2020); therefore, the repeatability and technical heterogeneity of results was not reported in the majority of studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Verbal episodic memory was assessed with the 12-word P(r)VLT (Bezdicek et al, 2014; Gifford Liu, Neal, Babicz, et al, 2018), a test constructed and administered consistent with the 9-word P(r)VLT and original 16-word CVLT (Delis et al, 1987). Visual episodic memory was assessed with the BVMT-R (Benedict, 1997).…”
Section: Methodsmentioning
confidence: 99%